The psychosocial development of adolescent siblings of children with spina bifida - Royle, Catherine M. (1990)
Thesis (M.N.)--Memorial University of Newfoundland, 1990. Nursing Bibliography: leaves 135-142. -- Error in pagination: duplicated pages after p.155 deleted from digital object. A qualitative research study was undertaken to describe the developmental experiences of adolescents who have a sibling with spina bifida and to examine the impact of having a physically disabled sibling on the development of such adolescents. The developmental tasks of Duvall and Miller (1985) provided a conceptual framework for exploring the developmental experiences of adolescents and sorting and analyzing the data. -- Eleven adolescents, with the approval of their parents, participated in the study which involved tape recorded interviews. The guided interview process was utilized to obtain descriptions of the adolescents' experiences related to their development. -- The analysis revealed that the adolescents were in the process of achieving the developmental tasks appropriate for their age group. The experience of living with a child with a physical disability did have some impact on specific developmental tasks. Many of the adolescents demonstrated a maturity in development of specific tasks and this may be related to the experience of living with a child with a physical disability. Having a sibling with spina bifida has an impact upon six major areas during adolescence: 1) family responsibilities, 2) parental relationships, 3) sibling interaction, 4) school, 5) friends and peers, and 6) personal maturation.